Growth diagrams of Indonesian children The nationwide survey of 2005 - Jose Batubara; Anna Alisjahbana; AngÃ¨le JGMGerver-Jansen; Bachti Alisjahbana; Tony Sadjimin; Yulniar Tasli; Juhariah Juhariah; Angky Tririni; Woro Indri Padmosiwi; Tya Listiaty; Henriette A Delemarreâ€“van de Waal; Willem J Gerver (Indonesian Pediatric Society, 2006)
Background Reference curves of growth have been developedin many countries based on cross-sectional data. The World HealthOrganization (WHO) has recommended an international referencewhich is based on the growth standards developed within the UnitedStates during the 1970s. In general these growth references areused in Indonesian pediatric clinics although it is known that thesereferences are not appropriate for this population with a differentethnic background. In order to evaluate reliably Indonesian chil-dren with growth disorders reference standards based on mea-surements in Indonesian children are necessary.Objective To make a standard growth chart for Indonesian chil-dren especially with regards to height, weight, and head circum-ference from a healthy Indonesian infants and children, age 0-18years. This standard charts were compared to CDC growth charts.Methods Weight and height and head circumference were takenfrom children with age ranging from birth up to 18 years. All sub-jects were recruited from 7 different parts of Indonesia. The agegrouping for children from 0-1 years old was based on 3-monthinterval, while for children older than 12 months was based on a 6-month interval. The study was cross sectional.Results There were 34 800 children (17 229 boys and 17 571girls) included in this study with age ranging from 0 up to 18 years.Graphs were presented for weight for age, supine length for age,head circumference for age in male and female infants, and weightfor height and height for age in boys and girls 1-18 years.Comparson of the results of this study with the CDC data werepresented as a graph.Conclusion The standard charts for Indonesian children basedon weight for height, supine length for height and head circumfer-ence for age were presented in graphs for children 0-1 year, weightfor height and height for age for boys and girls 1-18 years old. Allchildren were compared to CDC growth charts and there exists amean difference of -1.47 SDS for boys and -1.43 SDS forgirls.